Krugman on the Liquidity Trap: Why Inflation Won't Bring Recovery In Japan - Jan A. Kregel (Levy Economics Institute of Bard College, 2000)
Paul Krugman has argued that Japan is in a liquidity trap and that it can recover only if the central bank there follows a policy of "credible inflation." This paper argues that Krugman's proposal, which is similar to what Fisher proposed during the depression, is based on a different interpretation of the liquidity trap from that proposed by Keynes and as a result his policy recommendations can result in neither the elimination of the trap nor in Japan's economic recovery.
Keywords: 330